The Influence of Destination Image, Food Image, and Perception on Revisit Intention on Culinary Tourism at Permindo Night Market in Padang City - Dhini Denisa; Verinita Verinita (Inovbiz: Jurnal Inovasi Bisnis Seri Manajemen, Investasi dan Kewirausahaan, 2021)
This study aims to see the influence of the Food Image, Perception and Destination image on the Revisit intention of consumers at Permindo night market in Padang. Research objects are consumers who have visited Permindo Night Market Padang and the research samples taken are consumers who have visited Permindo Night Market Padang, who are members of The Happy Store. The sampling technique used was purposive sampling technique, in which the selected sample was purposely determined based on predetermined criteria in order to obtain a representative sample. The data used is cross section data. The data collection technique is to collect data directly with the field method (field research) where the questionnaire is distributed directly to the members of The Happy Store who have visited Permindo Night Market, Padang, represented by 205 respondents. The data analysis technique used is the frequency distribution, validity test, reliability test, multiple linear regression analysis, F&T test and the coefficient of determination (R2). The result of this research is that food image and perception have no effect on revisit intention, while destination image affects revisit intention.Keywords: Food Image, Perception, Destination Image, Revisit Intention.